Fenomena Politik Cebong dan Kampret di Indonesia: Sebuah Analisis dari Perspektif Pemikiran Politik dalam Islam - Hamid, Abdulloh; Darwis, Darwis; Andriyani, Santi (POLITEA, 2018)
Labelling cebong and kampret among supporters of Joko Widodo and Prabowo Subianto has been stronger in political phenomenon of Indonesia. This research aims to compare the political polarization after death of Prophet Muhammad with political polarization which is happening right now in Indonesia by using approach of Islamic political thought. This research also used library research as methodology of research to analyse the equal between bhoth phenomena in order to take lesson from the old phenomenon in mainting the unity of people in contemporary phenomenon exactly in Indonesia. The research found that to gain political power always cause polarization and conflict among people within society. Indonesian must learn from it to safeguard the unity of Indnesia as nation state           Keywords: Cebong, Kampret, Politic, Islamic Political Thought